The sound power of a circular plate for high-frequency wave radiation - RDZANEK, Witold (Archives of Acoustics, 1983)
This paper gives an analysis of the sound power of a circular plate which vibrates at a frequency much higher than the resonance one. This analysis was carried out for Bessel axially-symmetric distributions of vibration velocity on the surface of a source placed in a rigid, planar baffle. An exact expression of the sound power of the vibrating circular plate was given in Hankel representation. It was assumed in a specific case that the source radiated waves at frequencies much higher than the resonance ones, permitting simplifications to be introduced in the subintegral function. As the final result of the analysis, an approximate expression was derived using the Cauchy theorem on residua. The expressions derived here are very useful and convenient for numerical calculations.